2009
DOI: 10.3354/dao02120
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of change to coral communities off Mona and Desecheo Islands, Puerto Rico, from disease and bleaching

Abstract: Remote reefs off southwest Puerto Rico have experienced recent losses in live coral cover of 30 to 80%, primarily due to the decline of Montastraea annularis and M. faveolata from disease and bleaching. These species were formerly the largest, oldest, and most abundant corals on these reefs, constituting over 65% of the living coral cover and 40 to 80% of the total number of colonies. From 1998 to 2001, outbreaks of yellow band disease (YBD) and white plague (WP) affected 30 to 60% of the M. annularis (complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 38 publications
2
53
0
1
Order By: Relevance
“…Local impacts such as overfishing, nutrient and soil runoff from farms, municipal pollution and damage from tourist activities combine with the impacts of global climate change to cause degradation of coral communities (Gardner, Côte´, Gill, Grant & Watkinson, 2003;Burke & Maidens, 2004;Knowlton & Jackson, 2008;Burke et al, 2011;Jackson et al, 2012). Changes in global climate have resulted in ocean temperatures high enough to cause bleaching and stress to corals (Baker, Glynn & Riegl, 2008;Bruckner & Hill, 2009;Cantin et al, 2010;Eakin et al, 2010;Buddemeier, lane & Martinich, 2011;Riegl, Berumen & Bruckner, 2013). Local impacts such as increased nutrient levels have now been shown to increase sensitivity of corals to bleaching (Wiedemann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Local impacts such as overfishing, nutrient and soil runoff from farms, municipal pollution and damage from tourist activities combine with the impacts of global climate change to cause degradation of coral communities (Gardner, Côte´, Gill, Grant & Watkinson, 2003;Burke & Maidens, 2004;Knowlton & Jackson, 2008;Burke et al, 2011;Jackson et al, 2012). Changes in global climate have resulted in ocean temperatures high enough to cause bleaching and stress to corals (Baker, Glynn & Riegl, 2008;Bruckner & Hill, 2009;Cantin et al, 2010;Eakin et al, 2010;Buddemeier, lane & Martinich, 2011;Riegl, Berumen & Bruckner, 2013). Local impacts such as increased nutrient levels have now been shown to increase sensitivity of corals to bleaching (Wiedemann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…But several long-term studies have shown very limited sexual recruitment success for the O. annularis species complex (Rogers et al, 1984;Edmunds & Elahi, 2007;Irizarry-Soto & Weil, 2009), even at Mona Island (Bruckner & Hill, 2009). Edmunds (2004) also found a positive correlation between juvenile coral density and mean sea surface temperature (SST), with slower growth and higher mortality under high SST, in a pattern leading to changes in relative generic abundance.…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence that recent sea surface warming trends across the Caribbean associated with climate change resulted in significant shifts in coral reef benthic community structure due to the long-term impacts of the 2005 widespread massive coral bleaching that impacted at least 65% of the corals at Mona Island, including 94% of the colonies of the of Star coral Orbicella (=Mon-tastraea) annularis species complex (Ellis & Solander, 1786) (García-Sais et al, 2008). This event was followed by the 2005-2006 large-scale coral disease outbreak and mortality (Miller et al, 2009; Edmunds, 2013 (Bruckner & Bruckner, 2006;Bruckner & Hill, 2009). These factors led to massive coral recruitment failure of multiple species, resulting in a major decline in the natural recovery ability of critical reef-building species such as O. annularis (Edmunds & Elahi, 2007;Hernández-Pacheco, Hernández-Delgado, & Sabat, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental stress impairs coral host immunity and promotes pathogen virulence (Fitt et al 2001, Blanford et al 2003, Lafferty & Holt 2003, Ward et al 2007). As such, disease prevalence (predominantly tissue loss diseases) often increases during or proceeding coral bleaching events when temperatures are high and the coral hosts are compromised (Jones et al 2004b, Miller et al 2006, Whelan et al 2007, Brandt & McManus 2009, Bruckner & Hill 2009, Cróquer & Weil 2009). At Palmyra, overall disease prevalence within our permanent transects was higher in 2009 than 2008 (by 0.14%).…”
Section: Disease Severity Fate and Temporal Patternsmentioning
confidence: 99%